Experimental measurement of oil spill spreading in a wawe tank using digital image processing - Andreatta, A.; Saavedra, L.; Flores, H.; Llona, G. (Revista de la Facultad de Ingeniería UCV, 2018)
In this work, an experimental study of spreading of crude oil is carried out in a wave tank. The tests are performed by spilling different volumes and types of crude oil on the water surface. An experimental measurement technique was developed based on digital processing of video images. The acquisition and processing of such images is carried out by using a video camera and inexpensive microcomputer hardware and software. Processing is carried out by first performing a digital image filter, then edge detection is performed on the filtered image data. The final result is a file that contains the coordinates of a polygon that encloses the observed slick for each time step. Different types of filters are actually used in order to adequately separate the color intensities corresponding to each of the elements in the image. Postprocessing of the vectorized images provides accurate measurements of the slick edgc, thus obtaining a complete geometric representation, which is significantly different from simplified considerations of radially symmetric spreading. The spreading of the oil slick was recorded for each of the tests. Results of the experimental study are presented for each spreading regime, and analyzed in terms of the wave parameters such as period and wave height.